2015
DOI: 10.1186/s40064-015-1030-7
|View full text |Cite
|
Sign up to set email alerts
|

Oncorhynchus mykiss pax7 sequence variations with comparative analyses against other teleost species

Abstract: The paired box-7 (pax7) transcription factor expressed in satellite cells (SCs) is an essential regulator of skeletal muscle growth and regeneration in vertebrates including fish. Characterization of rainbow trout (Oncorhynchus mykiss) pax7 gene/s may offer novel insights into skeletal myogenesis by SCs in this indeterminate growth species. Further, evaluation of promoters for cis-regulatory regions may shed light on the evolutionary fate of the duplicated genes. Employing standard PCR, cloning and computation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Hindbrain development in teleosts is dependent on pax1 and pax9, whereas pax6 plays a role in retinal development (Lakowski et al 2007). Myogenesis is mediated by the expression of pax3 and pax7 (Kacperczyk et al 2009, Froehlich et al 2013, Chapalamadugu et al 2015, whereas pax8 is an early marker for inner ear growth and is also required for otic placode development (Mackereth et al 2005). For instance, pax2, in teleosts, plays an important role in several developmental processes such as retinal regeneration in the optic nerve head of goldfish (Parrilla et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Hindbrain development in teleosts is dependent on pax1 and pax9, whereas pax6 plays a role in retinal development (Lakowski et al 2007). Myogenesis is mediated by the expression of pax3 and pax7 (Kacperczyk et al 2009, Froehlich et al 2013, Chapalamadugu et al 2015, whereas pax8 is an early marker for inner ear growth and is also required for otic placode development (Mackereth et al 2005). For instance, pax2, in teleosts, plays an important role in several developmental processes such as retinal regeneration in the optic nerve head of goldfish (Parrilla et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been made to reveal the characteristics and regulatory mechanism of this molecule in a number of terrestrial animals including human (Homo sapiens; Pawlikowski et al, 2009), mouse (Mus musculus; Nicklas et al, 2012), pig (Sus scrofa domesticus; Ding et al, 2017), cow (Bos Taurus;Ramírez-Espinosa et al, 2016), chicken (Gallus gallus; Halevy et al, 2004). Furthermore, some studies have shown the genetic information of PAX7 in several fish species including zebrafish (Danio rerio; Berberoglu et al, 2017), Rainbow trout (Oncorhynchus mykiss; Chapalamadugu et al, 2015), longtail knifefish (Sternopygus macrurus; Weber et al, 2012), and gilthead sea bream (Sparus aurata; García de la serrana et al, 2014). However, the basic information of A. schlegelii PAX7 has not been verified yet and thus should be revealed for further research and development of this fish as a food material.…”
mentioning
confidence: 99%